Nietzsche: pathos artístico versus consciência moral - Krastanov, Stefan Vasilev (Universidade Federal de São Carlos, 2010)
The present work proposes an interpretation of the nietszchinian philosophy and, more specifically, of two fundamental and constitutive aspects of his thought, that are: the discussion about the language and the question about the tragic and the Greek tragedy. The reported interpretation is configured through a reading of split expressed as opposition between the artistic pathos and the ethical consciousness, justified by the proper title: Nietzsche, artistic pathos versus ethic consciousness. The artistic pathos is associated, mainly, with the pulsional strength that leads to the creation. This is the reason through what was chosen this notion, instead of the word art, putting in prominence that this isn t just a cultural phenomenon that the word art, usually means, but of an accomplishment of the life, itself (Wirklchkeit) from the creation. The work was developed in two parts, observing the two points emphasized in the research: the discussion about the language that focuses the relation between the metaphor and the concept, by a side, and the problem about the tragic connected to the pretension of the philosopher of denominating himself as the first tragic philosopher , by another. Coming from an analysis of these two points that arise in the young period of Nietzsche and, certainly, enunciate the future trajectory of his thought, we tried to show that Nietzsche- on the contrary of the affirmed by some commentators, among them, Heideggerachieved to break the theoretician conception subjacent to every philosophic thought since the ages of Socrates and Plato, through the powerful weapon of the art, that, here, by a peculiar reason is called artistic pathos.
Keywords: Filosofia - história; O Trágico; Metáfora; Conceitos; Consciência (Ética); Pathos artístico; Consciência moral; Artistic pathos; Ethical consciousness; The tragic; Metaphor; Concept; CIENCIAS HUMANAS::FILOSOFIA